1998
DOI: 10.1177/104346398010004005
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm for Social Capital

Abstract: This paper reconsiders James S. Coleman's concept of social capital. The concept has gained wide use and acceptance in sociology since its first publication, but, Coleman's own writings on the subject remain to date its most extensive analytic treatment. We make two contributions to social capital theory. First, we recast social capital theory to focus on benefits rather than forms. We identify three benefits that forms of social capital may confer: information, influence and control, and social solidarity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(123 citation statements)
references
References 26 publications
0
120
0
3
Order By: Relevance
“…Some research indicated that different types of social networks promote different positive outcomes (e.g., Sandefur and Laumann 1998), and the strength of these positive influences are found to differ in various contexts (e.g., Oishi and Kesebir 2012). For instance, Oishi and Kesebir (2012) found that weak social relationships are more effective in promoting better psychological well-being in more mobile and wealthier societies whereas deep social relationships are more important in less mobile and less wealthy societies.…”
Section: Future Directionsmentioning
confidence: 95%
“…Some research indicated that different types of social networks promote different positive outcomes (e.g., Sandefur and Laumann 1998), and the strength of these positive influences are found to differ in various contexts (e.g., Oishi and Kesebir 2012). For instance, Oishi and Kesebir (2012) found that weak social relationships are more effective in promoting better psychological well-being in more mobile and wealthier societies whereas deep social relationships are more important in less mobile and less wealthy societies.…”
Section: Future Directionsmentioning
confidence: 95%
“…Family ties, like business and government ties, can be utilised by entrepreneurs to establish their business and gain comparative advantage. Sandefur and Laumann (1998) summarises three benefits that social capital may confer: information, influence and control and social solidarity. They also suggest that social capital may vary in the degree to which its benefits generalize to different kinds of goals.…”
Section: Discussionmentioning
confidence: 99%
“…Sandefur and Laumann (1998) define social solidarity as something achieved 'among two or more individuals when there is a degree of mutual trust and commitment that is independent of any specific transaction' and that 'may arise out of conditions of repeated interaction among the same actors over time, during which forms of social capital such as trust and mutual obligations accumulate' (p. 491). Building on Coleman's (1988) theory of social capital, Sandefur and Laumann (1998) highlight social solidarity as one benefit of social capital that allows individuals to attain various goals, by fostering a sense of mutual obligation and reciprocity. There were participants in our study who did not express a sense of social solidarity with their co-workers.…”
Section: Social Solidaritymentioning
confidence: 99%
“…Although these participants often described their relations with co-workers as 'friendly', they did not perceive their coworkers as an 'extended family' or as 'best friends' as older participants did. It is possible that this is because they had not been exposed to 'conditions of repeated interaction among the same actors over time' (Sandefur & Laumann, 1998), which tend to foster feelings of solidarity. This was demonstrated in an excerpt from our FGD in Kharkiv:…”
Section: Social Solidaritymentioning
confidence: 99%